Best of enemies : the last great spy story of the Cold War - Russo, Gus; Dezenhall, Eric (Twelve, 2018)
"The story of two Cold War spies - CIA agent Jack Platt and KGB agent Genya Vasilenko - and their improbable friendship at a time when they should have been anything but."--Provided by publisher.